Советский политический плакат: комплект из 24 открыток / ред. Г. Малянтович] - Дмитриев Д. (Изогиз, 1957)
Экземпляры: ИСК (20050601) / Инвентарный номер: из1621 / Цена: 4.80 / Сис.шифр: 85.15 / Авт.знак: С 56 / ГРНТИ: 18 / ББК: 85.156.6